Surface- and deep-water hydrography and meltwater events in the mid-latitude North Atlantic Ocean over the past 160,000 years - Park, Myong-Ho; Kiefer, Thorsten; Zahn, Rainer (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2001)
An investigation involving stable oxygen and carbon isotopes on core Ml5612 from the Mid-Atlantic Ridge (445N, 26°W) shows that distinct negative S'^O anomalies punctuate the plank tonic isotope records and correlate with the icc-raftcd detritus (IRD) events. Within most IRD layers, detntal carbonate contributes between I and 13% and supports the contention thai the layers are the southern equivalents of the northern North Atlantic Ocean's Heinnch events Anomalies are strongest for the Neogloboquadrinapachyderma (sinistral coiling) isotope record. Systematic changes in the 6**0 offset between Globigerina bulloiJes and Giohorofalia inflata signify variations in the mid-latirudc thermocline structure. In conjunction with negative benthic 8nC anomalies, the data document a stronger contribution of an ''O-depleted, nutrient-rich water mass during the Hcinrich events. The 8MC amplitude of-~--l%© between 25 and 57 ka indicates changes between northern-source (North Atlantic Deep Water) and southern-source (Antarctic Bottom Water) water masses at this site. The Heinrich layers in the mid-latitude core arc correlative with those from a core off Portugal. This synchromcity may have resulted from common changes in a North Atlantic thermohaline switch.